Analisis Penerimaan Layanan Spaylater Menggunakan Model UTAUT 2 dan Dampaknya Terhadap Perilaku Online Impulse Buying : (Survey pada Pembelian Produk Fashion oleh Gen Z di Kabupaten Garut) - A'ini, Nurul Qurrota; Susilawati, Wati; Septiani, Hera Laxmi Devi (Universitas Hamzanwadi, 2025)
This study aims to analyze the acceptance of Spaylater using the UTAUT 2 model and evaluate its impact on online impulse buying (OIB) behavior among Gen Z in Garut Regency. A total of 400 Gen Z respondents who had purchased fashion products on Shopee using Spaylater as the payment method participated in this study. The analysis was conducted using Structural Equation Modeling (SEM) with the assistance of SmartPLS. Gen Z is known as a generation highly engaged with digital technology and strongly attracted to tech-based financial services, including Buy Now Pay Later features such as Shopee PayLater. The results show that social influence (SI) and habit (HB) significantly influence behavioral intention (BI). Beside that, habit (HB) and Behavioral Intention (BI) are significantly influence online impulse buying (OIB). Furthermore, hedonic motivation (HM) not influencing Behavioral Intention (BI), also Social Influence (SI) does not influencing Online Impulse Buying (OIB). These findings suggest that habits and peer pressure strongly affect Gen Z’s use of BNPL services, while fun or pleasure is not a major reason they choose to use them.